UPAYA-UPAYA PEMULIHAN DIRI MANTAN LESBIAN - Nurul Fatimah, Puti (Universitas Ahmad Dahlan, 2014)
ABSTRACT The goal of this research is to find out the cause of ex lesbian make serious effort to back in normal live and what kinds of effort that can be done by the lesbian to be a normal. This research used qualitative method. The research data are executed by observation and interview with two subjects with range of age between 17 years old until 21 years old and both of them are totally heal. The first conclusion of this research is the cause of the both subjects want to be recovered is being a lesbian is not guarantee that they can achieve the true happines, beside that being a lesbian, they will not give an offspring. Both of subjects will not endure with pressure and felt guilty, and will not survive with lesbian live. Guilty mind towards the family, peoples that they love even felt guilty with God. Second conclusion that the effort that be done by ex lesbian is made a commitment to change, self regulation, recognizing environment which able to help recovery effort, able to self control, and create the maintenance program.Keywords: Ex Lesbian